On the Dirac-like equation in 7-component space-time and generalized Clifford-Dirac algebra - Simulik, V.M. (Carpathian Mathematical Publications, 2023)
The generalized Dirac equation related to 7-component space-time with one time coordinate and six space coordinates has been introduced. Three 8-component Dirac equations have been derived from the same 256-dimensional Clifford-Dirac matrix algebra. Corresponding Clifford-Dirac algebra is considered in the Pauli-Dirac representation of 8 × 8 gamma matrices. It is proved that this matrix algebra over the field of real numbers has 256-dimensional basis and it is isomorphic to geometric C^R (1,7) algebra. The corresponding gamma matrix representation of 45-dimensional SO(1,9) algebra is derived and the way of its generalization to the SO(m,n) algebra is demonstrated. The Klein-Gordon equation in 7-component space-time is considered as well. The way of corresponding consideration of the Maxwell equations and of equations for an arbitrary spin is indicated.